Study on Elastic Deformation of Interstitial Alloy FeC with BCC Structure under Pressure - Nguyen, Quang Hoc (H. : ĐHQGHN, 2019)
The analytic expressions of the free energy, the mean nearest neighbor distance between two atoms, the elastic moduli such as the Young modulus E, the bulk modulus K, the rigidity modulus G and the elastic constants C11, C12, C44 for interstitial alloy AB with BCC structure under pressure are derived from the statistical moment method. The elastic deformations of main metal A is special case of elastic deformation for interstitial alloy AB. The theoretical results are applied to alloy FeC under pressure. The numerical results for this alloy are compared with the numerical results for main metal Fe and experiments